Down-shifting of Light by Ion Implanted Samples for Photovoltaic Applications - Savidge, Rachel M. (My University, 2012)
Single junction silicon photovoltaic cells (SJSPVCs) are unable to transform all the energy in the solar spectrum into electricity, due to the broad nature of the solar spectrum and the limits imposed by a single bandgap. Furthermore, high surface recombination velocity reduces the SJSPVC external quantum efficiency response, particularly to ultraviolet photons. It is the goal of spectral engineering to optimize the light that is incident on the cell, by down-shifting high energy photons to lower energies, for example, to improve the performance of photovoltaic cells.
This thesis represents a study into the luminescence of ion implanted films, involving silicon nanocrystals (Si-NCs) and rare-earth ions in fused silica or silicon nitride. Quantum efficiency measurements taken with an integrating sphere were used to characterize some of the samples. Other photoluminescence (PL) characterization work was carried out with a single-wavelength laser and a collection lens normal to the sample. Variable angle spectroscopic ellipsometry (VASE) was used to estimate the optical constants of the implanted films. In secondary work, Rutherford backscattering spectrometry, time-dependent PL, infrared-PL measurements, and electrical conductivity measurements were used to characterize select samples.
It was found that the conversion efficiency of Si-NCs in fused silica was about 1% – too low to be useful according to modeled results. However, considerable variation in the peak wavelength of the Si-NC PL was obtained, depending on the peak concentration of implanted silicon. Si-NC-type PL was also produced by low-energy implantation of oxygen into a Czochralski silicon wafer.
Oxygen was also implanted into films of cerium-doped high-purity silicon nitride, and it was shown that the photoluminescence from these films is largely dependent on the level of oxygen doping. The internal conversion efficiency of a cerium-doped fused silica sample was found to approach 20%, which indicates that this is a promising avenue for future research.
Finally, energy transfer was demonstrated between Si-NCs and erbium ions. The lifetime of the erbium PL appears to increase with increasing implanted silicon fluence.
Keywords: Photoluminescence; quantum efficiency; silicon nanocrystals; cerium; integrating sphere; ion implantation; Engineering Physics; Engineering Physics